The Sooner, the Better? Couples' First Financial Discussion, Relationship Quality, and Financial Conflict in Emerging Adulthood - Matthew T. Saxey; Ashley B. LeBaron-Black; Melissa A. Curran (Journal of Financial Therapy, 2022)
In couple relationships, discussing finances is often considered taboo. Specifically, emerging adult couples experience several unique financial challenges that may contribute to poorer financial communication and pose relational risks. Utilizing structural equation modeling with a sample of 1,950 U.S. emerging adults, the current study tests associations between the time of a couple’s first financial discussion, financial communication, relationship quality, and financial conflict. Results indicate that initiating financial discussion earlier in a romantic relationship may benefit relationship quality—through financial communication. However, having an earlier first financial discussion as a couple was also positively associated with financial conflict. Financial therapists might consider teaching emerging adult couples to have a first financial discussion earlier along with strategies to overcome financial conflict. Additionally, financial therapists may consider assessing when emerging adult couples first discussed finances in their relationship. Overall, our findings suggest the sooner an emerging adult couple discusses finances, the better.
Keywords: emerging adulthood; financial communication; financial conflict; financial discussion; relationship quality